Static-dynamic strain response to the 2016 M6.2 Hutubi earthquake (eastern Tien Shan, NW China) recorded in a borehole strainmeter network. (1st October 2019) - Gong, Zheng; Jing, Yan; Li, Haibing; Li, Li; Fan, Xiaoyong; Liu, Zheng
Graphical abstract: Highlights: Static strains show the seismogenic fault is a north-dipping backthrust fault. The peak dynamic strains decay faster in E-W than N-S direction. The decaying behavior of the ratio static/dynamic is complicated. Abstract: The 2016 M6.2 Hutubi Earthquake is an event occurred on a reverse fault located in the northern Chinese Tien Shan, but it is debatable whether the seismogenic fault is a low-angle thrust fault. The coseismic strain responses have been recorded by nine 4-component RZB borehole strainmeters, locating 11–320 km away from the epicenter. The nearest four stations have recorded resolvable static strain responses. The authors used the theoretic tide to calibrate the strains, and relocated the 10.31 km by 6.85 km fault plane through a grid-search method. Two groups of fault parameters 279°/70°/87° and 103°/28°/85° were obtained, and the predictions for 24/26 channels for both groups are consistent with the offsets observed in the near stations by correcting the azimuths. The seismogenic fault is more likely the high-angle backthrust fault based on the comparison with the selected aftershocks. Furthermore, all strainmeters have recorded the dynamic strain waves. The dynamic strains are sensitive to the seismic wave propagation direction, and the peak dynamic strains decay faster in the N-S direction than that in the E-W direction due to the regional structure features. The absolute static strains are comparable to the dynamic strains in the near field, but the ratios between them decrease remarkably in the intermediate and far field. The difference in the dependence on distance was found to be useful to differentiate static strains from dynamic strains.